EFEITO OROGRÁFICO NA ILHA DE SÃO SEBASTIÃO (ILHABELA – SP) - Marcos Alexandre MILANESI; Emerson GALVANI (Revista Brasileira de Climatologia, 2011)
This article aims at assessing, in the relationship between rain versus relief, the occurrence of orographic precipitation on the windward side of the Island of São Sebastião (Ilhabela - SP). Throughout the Hydrologic Year 2004 - 2005 rainfall data were collected monthly, through the installation of six experimental rain gauges in Castelhanos Road - guidance W - E, with 22 km and maximum altitude of 690m, at different altitudes. The data were descriptive statistics and their synthesis led essentially to three results: 1) more than a half or 60.1% of the total rainfall collected was precipitated on the exposed side of the SE sector flows (windward) confirming the importance of the relief in its distribution; 2) rain shadow description through the reduction of rainfall in the lee of the island, where the values collected were 20% lower than the opposite side, and 3) identification of orographic rain at 600m altitude (P7), where the collected values were invariably higher than the others, around 30% higher, exceeding 4000 mm per year and reaching a total monthly of 708.5 mm in March 2005.